Palembang Malay Literature and Arts as a Living Ecosystem of Malay Islamic Civilization - Nandika Putra Pratama; Ainun Mar’atus Soleha; Syahratus Sita; Choirun Niswah (CV. Jalan Cendikia, 2026)
This study examines Palembang Malay literature and art as expressions of Malay Islamic civilization. It focuses on three main issues: the reflection of Islamic values in Palembang Malay literary traditions, the representation of Malay Islamic aesthetics in songket and traditional performing arts, and the mechanisms through which Islamic civilizational values are transmitted in contemporary Palembang society. This research employed a qualitative method with an ethnographic approach. Data were collected through semi-structured interviews with six key informants, participatory observations, and documentation studies involving manuscripts, songket motifs, dance, music, and customary-religious practices. The findings show that syair, pantun, and Malay manuscripts function as media for transmitting tawhid, morality, Sufism, religious advice, and Islamic historical memory. Palembang songket represents Islamic aesthetics through motifs, colors, materials, and ritual uses, while Gending Sriwijaya Dance, Tanggai Dance, and Batanghari Sembilan Music embody values of humility, respect, gentleness, patience, and spiritual devotion. The transmission of these values takes place through family, art studios, customary-religious ceremonies, pesantren and taklim assemblies, and formal institutions. This study concludes that Palembang Malay literature and art form a living cultural ecosystem that connects Islamic values, Malay identity, collective memory, and social practice.